2013
DOI: 10.1179/1754762813y.0000000040
|View full text |Cite
|
Sign up to set email alerts
|

Sound localization with bilateral cochlear implants in noise: How much do head movements contribute to localization?

Abstract: Bilateral cochlear implant (CI) users encounter difficulties in localizing sound sources in everyday environments, especially in the presence of background noise and reverberation. They tend to show large directional errors and front-back confusions compared to normal hearing (NH) subjects in the same conditions. In this study, the ability of bilateral CI users to use head movements to improve sound source localization was evaluated. Speech sentences of 0.5, 2, and 4.5 seconds were presented in noise to the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Each direction was tested five times, so each run included 70 stimulus presentations for the EAS group and 35 presentations for the NH, respectively. The subjects were asked to turn their heads to the midline and to visually fixate an initial active LED at 0˚prior to sound presentation to avoid additional cues from head movements [32]. The perceived direction was recorded using a pointing method adapted from the method proposed by Seeber et al [33].…”
Section: Sound Localization Setupmentioning
confidence: 99%
“…Each direction was tested five times, so each run included 70 stimulus presentations for the EAS group and 35 presentations for the NH, respectively. The subjects were asked to turn their heads to the midline and to visually fixate an initial active LED at 0˚prior to sound presentation to avoid additional cues from head movements [32]. The perceived direction was recorded using a pointing method adapted from the method proposed by Seeber et al [33].…”
Section: Sound Localization Setupmentioning
confidence: 99%
“…For bilateral hearing aid users (both ears), each device works independently, which has destructive effects on the binaural cues necessary to locate sound [1]. Even bilateral cochlear implant users encounter difficulties in localizing sound [8,21]. Multisensory hearing devices have also been proposed, such as to direct amplification based on eye gaze [10]; this still requires the user to know where to look.…”
Section: Hearing Aids and Cochlear Implantsmentioning
confidence: 98%
“…Knowing where to focus visual attention is a prerequisite for effective speechreading. While hearing aids and surgically implanted devices can improve speech recognition, they generally do not improve sound localization [21,23]. In this paper, we investigate visualizations on a head-mounted display (HMD) to increase sound awareness for the deaf and hard of hearing, particularly for group conversations with oral partners.…”
Section: Introductionmentioning
confidence: 99%
“…Several psychoacoustic studies demonstrate that head motion increases sound localization in humans (Pollack & Rose 1967;Perrett & Noble, 1997a;1997b;Wightman & Kistler 1999;Vliegen et al, 2004;Brimijoin at al., 2013;Honda et al, 2013;McAnally & Martin, 2014), and monkeys (Populin, 2006). Speech perception improvements have also been documented (Munhall et al, 2004), even on patients with hearing aids (Mueller et al, 2014). Finally, head movements also proved important for the experience the surrounding ambient sound (Suzuki et al, 2011) and are starting to be implemented in machine-hearing systems (Ma et al, 2015).…”
Section: Head-movementsmentioning
confidence: 99%
“…Previous studies have shown that head movements help normal hearing listeners to distinguish between sounds coming from front and rear positions (Makous & Middlebrooks 1990;Mueller et al, 2014;Bronkhorst 1995;Mackensen, 2004;Perrett & Noble 1997a;Wallach 1940;Wenzel et al, 1993;Wightman & Kistler, 1999). Frontback confusion is removed if head movements were larger than 5° (Perrett & Noble, 1997a), and if sounds were long enough (Muller et al, 2014;Perrett & Noble, 1997a).…”
Section: Active Listening Improves 3d Sound Localizationmentioning
confidence: 99%